Ernesto Volkening, Reader of Nicolás Gómez Dávila. Journal, Brief Argumentative Forms, and Essay (2023)
Ernesto Volkening read, rewrote, and commented on Escolios a un texto implícito of Nicolás Gómez Dávila, a reading journal-based interpretive work with aphoristic and critical ambitions. This article recalls the content of his evaluations and highlights the importance they serve in defining glosses, maxims, and aphorisms. In addition, it focuses on the desire for the style of the fragments that are part of his work. The preceding supports the assessment of the form of writing in Volkening’s critical tasks and the reinforcement of the links between the reading journal, brief argumentative forms, and the essay.